Pemaknaan Konsumen Generasi Z Terhadap Pesan Afirmasi Positif Pada Kemasan Minuman Starbucks - Ni Made Vania Shinta Mahadewi; Ni Wayan Yuli Anggreni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to describe how Generation Z consumers interpret the positive affirmation messages written on Starbucks beverage cups using Stuart Hall’s encoding–decoding framework. Affirmative messages, initially designed as part of the brand’s emotional communication strategy, are often interpreted differently by audiences, making it important to understand the dynamics behind these varying interpretations. This research employed a descriptive qualitative approach involving Generation Z consumers, baristas, and a store supervisor. Data were collected through in-depth interviews and direct observations at several Starbucks outlets. The findings indicate that the encoding process is carried out by baristas as part of a service strategy intended to create a warm, personal, and pleasant customer experience. However, the decoding process resulted in three categories of meaning: dominant-hegemonic, negotiated position, and oppositional position. Consumers in the dominant position viewed the affirmations as genuine emotional support; those in the negotiated position interpreted the messages situationally; while those in the oppositional position rejected them as mere branding strategies. The study concludes that the effectiveness of affirmation messages depends on the perceived authenticity of the brand and the emotional state of the consumers, demonstrating that even simple packaging can become a complex medium of communication for a critical generation such as Gen Z.